DURIO MACRANTHA KOSTERM., SPECIES NOYA (BOMBACACEAE) FROM NORTH SUMATRA - kostermans, a. j. g. h. (Research Center for Biology, 1992)
An interesting species of Durio from Sumatra is described and illustrated from a living specimen growing in Bogor.